2009
DOI: 10.1186/1471-2172-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut health immunomodulatory and anti-inflammatory functions of gut enzyme digested high protein micro-nutrient dietary supplement-Enprocal

Abstract: BackgroundEnprocal is a high-protein micro-nutrient rich formulated supplementary food designed to meet the nutritional needs of the frail elderly and be delivered to them in every day foods. We studied the potential of Enprocal to improve gut and immune health using simple and robust bioassays for gut cell proliferation, intestinal integrity/permeability, immunomodulatory, anti-inflammatory and anti-oxidative activities. Effects of Enprocal were compared with whey protein concentrate 80 (WPC), heat treated sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Quick renal clearance is one of the major hurdles faced while using these molecules in humans and rodents. 30,36 Considering its anti-cancer properties, natural availability, and its immunemodulation and immune-enhancing capacities, bLf is one of the ideal proteins that can be used to achieve maximum anti-cancer effects, without causing any toxicity to surrounding normal cells and tissues. Various studies on bLf, a natural milk protein, have proved its anti-cancer effects and lack of toxicity to normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quick renal clearance is one of the major hurdles faced while using these molecules in humans and rodents. 30,36 Considering its anti-cancer properties, natural availability, and its immunemodulation and immune-enhancing capacities, bLf is one of the ideal proteins that can be used to achieve maximum anti-cancer effects, without causing any toxicity to surrounding normal cells and tissues. Various studies on bLf, a natural milk protein, have proved its anti-cancer effects and lack of toxicity to normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fe-bLf and Apo-bLf were loaded on the silk NPs with 10% w/w ratio, as determined by a previous study done in our laboratory. 30 The mixture (silk NPs + Fe-bLf or silk NPs + Apo-bLf) was incubated for 48 hours with slow stirring (30 rpm) at 4°C. After 48 hours, the samples were collected and centrifuged at 1,500 rpm for 20 minutes.…”
mentioning
confidence: 99%
“…The ingredients of Enprocal are dairy-based proteins (Whey protein concentrate, skim milk powder, whole milk powder), vitamins and minerals (calcium, zinc, vitamins C, D, B and A), vegetable oils and inulin. An in vitro study suggested that Enprocal displays some immunomodulatory properties on immune cells (Kanwar & Kanwar, 2009). Lactoferrine has also important immune modulator protein.…”
Section: How Living Habits and Nutrition Status Impact On Immune Funcmentioning
confidence: 99%
“…One of the most intriguing evidences about the role of CD57+ T lymphocytes in cancer comes from the fact that metastasis-free regional lymph nodes draining different human epithelial tumors present a reduction in almost all immune cells, except CD57+ lymphocytes (Kanwar & Kanwar, 2009). CD8+CD28-CD57+ T lymphocyte clones may be the result of persistent stimulation by tumor-associated antigens, combined with a reduced cellular death rate secondary to reduced expression of the apoptosis-related molecule CD95.…”
Section: Immunosenescence and Cancermentioning
confidence: 99%
“…The TEER protocol was followed from our previous study. 32 The ex vivo loop assay was performed by injecting rhodamine-labeled nanoparticles in rat intestinal loops (detailed methodology is described in the "Supplementary materials" section).…”
Section: Preparation and Characterization Of Sr9-loaded Chnpmentioning
confidence: 99%